Biomechanical indicators for the selection of talents in Colombian schoolchildren from 11 to 15 years old/Indicadores biomecánicos para la selección de talentos en escolares colombianos de 11 a 15 años - Samuel Villamarin Menza; José Alcibíades Acero Jauregui; Bergelino Zaldívar Pérez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
The selection of talents is carried out on the basis of biological, psychological, sociological and technical indicators. The objective of the study was to establish the level of correlation between running speed and some jumps for the selection of children sprinters in athletics. It is a descriptive, cross-sectional and correlational study, in which 335 children of both sexes from 11 to 15 years old participated. They were evaluated through tests such as weight and height, Abalakov jumps, unilateral right, unilateral left, bilateral and the bilateral deficit was calculated for which the contact platform was used. As results, it is highlighted that the biomechanical indicators, both in jumping height and in calculated power, increase with chronological age, although some variables show a decrease at 15 years. In the bilateral deficit, the results were rated as lower fair for girls and fair for boys. The correlation analysis between jumps and running speed showed significant correlations in girls (p<0.01) in the right unilateral jump in height and power, left unilateral jump in height and bilateral jump in power. In boys, correlations were found at the level (p<0.01) in Abalakov jump power, right unilateral jump power, left unilateral jump power, and bilateral jump power. In conclusion, according to the results and the literature, it can be stated that the jumps can be used as indicators in the selection of talents.